2017
DOI: 10.3390/toxins9040127
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Susceptibility of Field Populations of Helicoverpa armigera to Bacillus thuringiensis Vip3Aa Toxin and Lack of Cross-Resistance between Vip3Aa and Cry Toxins

Abstract: The cotton bollworm Helicoverpa armigera (Hübner) is one of the most damaging cotton pests worldwide. In China, control of this pest has been dependent on transgenic cotton producing a single Bacillus thuringiensis (Bt) protein Cry1Ac since 1997. A small, but significant, increase in H. armigera resistance to Cry1Ac was detected in field populations from Northern China. Since Vip3Aa has a different structure and mode of action than Cry proteins, Bt cotton pyramids containing Vip3Aa are considered as ideal succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
1
16
1
Order By: Relevance
“…[62][63][64] Mahon et al 51 found that Vip3A-resistant populations of H. armigera and H. punctigera had no cross-resistance to Cry1Ac and Cry2Ab. Wei et al 65 also reported that H. armigera with high levels of resistance to Cry1Ac or Cry2Ab had no cross-resistance to Vip3A. The lack of cross-resistance is also consistent with the results of Jackson et al 66 who found no cross-resistance to Vip3A in three H. virescens populations selected for resistance to Cry1Ac and/or Cry2Ab proteins.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…[62][63][64] Mahon et al 51 found that Vip3A-resistant populations of H. armigera and H. punctigera had no cross-resistance to Cry1Ac and Cry2Ab. Wei et al 65 also reported that H. armigera with high levels of resistance to Cry1Ac or Cry2Ab had no cross-resistance to Vip3A. The lack of cross-resistance is also consistent with the results of Jackson et al 66 who found no cross-resistance to Vip3A in three H. virescens populations selected for resistance to Cry1Ac and/or Cry2Ab proteins.…”
Section: Discussionsupporting
confidence: 73%
“…found that Vip3A‐resistant populations of H. armigera and H. punctigera had no cross‐resistance to Cry1Ac and Cry2Ab. Wei et al . also reported that H. armigera with high levels of resistance to Cry1Ac or Cry2Ab had no cross‐resistance to Vip3A.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also demonstrated that the colonies resistant to Cry1A proteins, Cry2Ab proteins ( T. ni and H. armigera ) or Dipel ( O. furnacalis , H. armigera , Plodia interpunctella, and T. ni ) had no cross‐resistance to Vip3 proteins (Gomis‐cebolla et al, ; P. Wang et al, ; Tables S3, S4). Several colonies of H. armigera with resistance to either Cry1Ac or Cry2Ab were also not cross‐resistance to Vip3Aa (An et al, ; Q. Zhang, Chen, Lu, Zhang, & Liang, ; Wei, Wu, Yang, & Wu, ; Table S3). Meanwhile, lack of cross‐resistance to Vip3A proteins was found in S. Frugiperda , which showed resistance to Cry1F or Cry2Ab2 in a series of studies (Bernardi et al, ; Vélez et al, ; Yang, Kerns, Head, & Brown, ; Yang, Kerns, Head, Price, & Huang, ).…”
Section: Cross‐resistance Between Cry and Vip Toxinsmentioning
confidence: 99%
“…Diet incorporation method was used for conducting bioassay, which is similar to the methods established for the baseline susceptibility of Helicoverpa armigera to B. thuringiensis toxins (Wei et al 2017). Seven concentrations (0.25, 0.50, 1, 2, 4, 8, 16 μg ml −1 ) of Cry1Ac and a control were prepared.…”
Section: Diet Incorporates Bioassaysmentioning
confidence: 99%